The Correlation between Environmental Sanitation and Stunting Management through Women's Interventions and Food Security in Pre-School Age Children - Rizdya Oktofani; Hartati Kartikaningsih; Nurul Badriyah (Postgraduate, University of Mataram, 2025)
Stunting is a chronic nutritional deficiency that impedes growth and affects the development of body and brain cells. Addressing stunting requires multisectoral collaboration to reduce and prevent stunting among children under 5 years old, the critical